2010
DOI: 10.1001/archoto.2009.214
|View full text |Cite
|
Sign up to set email alerts
|

Oncolysis Using Herpes Simplex Virus Type 1 Engineered to Express Cytosine Deaminase and a Fusogenic Glycoprotein for Head and Neck Squamous Cell Carcinoma

Abstract: Background A replication-competent, attenuated, oncolytic herpes simplex virus-1, OncoVEXGALV/CD, has previously been engineered to express a fusogenic protein from the gibbon ape leukemia virus and cytosine deaminase/uracil phosphoribosyltransferase (CD/UPRT) which converts fluorocytosine (5-FC) to 5-fluorouracil (5-FU). OncoVEXGFP is an analogous vector that expresses enhanced green fluorescent protein. Methods We assessed the ability of OncoVEXGALV/CD and OncoVEXGFP to infect, replicate within, and lyse f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…In animal models, tumor growth was reduced significantly in groups treated with M012 and 5-FC when compared to groups treated with the parental (unarmed) virus and drug [191]. Another oncolytic HSV-1 armed with CD, OncoVEX(GALV/CD), showed enhanced cytotoxic effects in vitro when used in combination with 5-FC in head and neck squamous carcinoma cell lines that were less susceptible to the oncolytic effects of the virus [192]. An armed VSV expressing a CD/UPRT fusion gene combined with 5-FC also reported enhancement of cell killing and a considerable bystander effect in vitro .…”
Section: Combination Therapy With Ovs and Drugs: More Than The Summentioning
confidence: 99%
See 1 more Smart Citation
“…In animal models, tumor growth was reduced significantly in groups treated with M012 and 5-FC when compared to groups treated with the parental (unarmed) virus and drug [191]. Another oncolytic HSV-1 armed with CD, OncoVEX(GALV/CD), showed enhanced cytotoxic effects in vitro when used in combination with 5-FC in head and neck squamous carcinoma cell lines that were less susceptible to the oncolytic effects of the virus [192]. An armed VSV expressing a CD/UPRT fusion gene combined with 5-FC also reported enhancement of cell killing and a considerable bystander effect in vitro .…”
Section: Combination Therapy With Ovs and Drugs: More Than The Summentioning
confidence: 99%
“…Other armed viruses expressing other therapeutic genes such as second mitochondria derived activator of caspases (Smac) [196], manganese superoxide dismutase (MnSOD) [197] and even viral fusion proteins by themselves or along with the CD transgene [192, 198], have also been tested in combination with 5-FU chemotherapy and shown to be effective. Combination of two GEPT systems has also been reported.…”
Section: Combination Therapy With Ovs and Drugs: More Than The Summentioning
confidence: 99%
“…A phase II clinical trial for patients with unresectable metastatic melanoma showed 26% response rate [60]. Moreover, a phase III clinical trial showed significant prolonged overall survival for unresectable metastatic melanoma [27,54].…”
Section: Oncolytic Virus Therapymentioning
confidence: 99%
“…Before these clinical trials, mouse models were used to investigate oncolytic activity. Most previous preclinical studies used human HNSCC cell lines implanted into the flank of immunodeficient mice [13][14][15][16][17][18][19][20][21], or murine SCC-VII cells [22][23][24][25]; however, they did not investigate the immune response. Furthermore, no study to date has used primarycultured cells obtained from surgical specimens.…”
Section: Introductionmentioning
confidence: 99%